Simultaneous Thalamic and Posterior Subthalamic Electrode Insertion With Single Deep Brain Stimulation Electrode for Essential Tremor. Issue 3 (17th September 2012) - Chang, Won Seok; Chung, Jong Chul; Kim, Joo Pyung; Chang, Jin Woo
<x xml:space="preserve">Abstract</x> Objectives: The optimal target location of deep brain stimulation (DBS) is the subject of some controversy. We implanted electrodes that could stimulate both posterior subthalamic area (PSA) and ventralis intermedius nucleus of thalamus (Vim), and examined the benefits of bilateral DBS of Vim, PSA, and Vim + PSA in patients with essential tremor (ET). Materials and Methods: Electrodes were inserted into the Vim and PSA in ten hemispheres of five consecutive patients. All patients were assessed for action tremor, including postural and kinetic tremors, both preoperatively and at six months and one year postoperatively. Results: The preoperative mean postural tremor score was 1.9 (range 1.0–2.5) and kinetic tremor score was 2.6 (range 2.0–3.0). One year after surgery, these scores had decreased significantly to 0.1 (range 0.0–1.0) and 0.6 (range 0.0–1.5), respectively. The postural and kinetic tremor scores at six‐months and one‐year post‐surgery were similar for Vim, PSA, and Vim + PSA stimulation. Conclusions: We were able to identify the optimal electrode placement site for each patient based on his or her individualized response to the stimulation. Overall, there was no statistically significant difference among the DBS sites in terms of the benefits afforded by the stimulation. We propose that our technique may be a useful surgical method to treat ET.